Enhanced ductility of WMoCu alloy through the formation of nanometer-to-micrometer-thick dual-phase transition phase layer - Jin Cao; Jinxu Liu; Chuan He; Shukui Li; Zehui Hao; Xinying Xue (Materials & Design, 2019)
Adding an appropriate interfacial layer is a viable way to decrease the WW contiguity and enhance the interfacial bonding of WCu alloy simultaneously, hence increase the tensile ductility. In this regard, we prepared a new kind of WMoCu alloy with transition phase (TP) existing between W particles and Cu matrix using infiltration method. The TP consisting of amorphous and nanocrystalline structure is formed between the W particles and the Cu matrix. The formation of the TP simultaneously decreases the WW contiguity and enhances bonding with both W particles and Cu matrix, leading to the good tensile ductility of the WMoCu alloy. The underlying formation mechanism of the TP is thoroughly studied. The WMoCu alloy exhibits excellent ductility under both compressive and tensile loading at room temperature. Under the quasi-static tensile loading, the critical failure strain of the WMoCu alloy is 0.18. Our analysis demonstrates that a strong bonding is formed between the TP and the adjacent phases. Keywords: WMoCu alloy, Transition phase, Amorphous and nanocrystalline phase, Interfacial bonding, Tensile ductility